Basic knowledge of travel agency management - 3G E-Learning LLC (New York, NY 3G E-Learning LLC, 2024)
"This book is a comprehensive guide that covers the essential aspects of managing a travel agency. It consists of eight chapters that provide an in-depth understanding of travel agency operations." --
Introduction to travel agency management.
Business planning for travel agencies.
Operations and administration of travel agencies.
Travel products and services.
Sales and marketing in travel agencies.
Human resources management in travel agencies.
Financial management and accounting for travel agencies.
Crisis management and risk assessment in travel agencies.
Index.
Editorial board: Aleksandar Mratinkovic, Dan Piestun, Hazem Shawky Fouda, Felecia Killings, Dr. Sandra El Hajj, Fozia Parveen, Igor Krunic, Dr. Jovan Pehcevski, Dr. Tanjina Nur, Stephen and Michelle.
Includes bibliographical references and index.
Keywords: Travel agency -- Management